UTERUS BIKORNU - Herti Marni; Ferdinal Ferry; Bobby Indra Utama (Universitas Andalas, 2019)
Background : Uterus bicornis subseptum is a deformity of the uterus such as the shape of the heart, the fundus appears to be curved inward, and has a barrier or wall inside to the uterine cavity. This abnormality occurs due to failure of the fusion of the left and right mullerian ducts. If pregnant, women who have this form of the uterus will usually experience a location abnormality, in which the fetus is often transverse or breech. However, women who have this disorder sometimes find it difficult to get pregnant so they experience infertility. In addition, there is usually a disturbance in the formation of the kidneys, but in this patient there was no abnormality in the urinary tract. In cases where the patient does not have children and a bicornu uterine abnormality is found, uterine repair is performed and it is hoped that with the uterine anatomy returning to normal, the patient can become pregnant.Objective : Discuss the management of cases of congenital abnormalities of the internal genital organs in patients with a bicornu uterus.Method : Case Report.Case : Reported a patient aged 25 years with primary infertility 4 years and a bicornu uterus. In patients, chromotubation was performed first, after chromotubation, the patient was performed metrosplasty to remove the bulkhead in the uterus and to repair the uterus. During the post-op follow-up at the hospital the patient did not show any signs of infection or acute abdomen, then the patient was discharged on day 5. The patient was advised to go to the OBGYN polyclinic regularly for further follow-up to the success of his uterine repair. Assessment can be done in several ways including transvaginal ultrasound to assess whether there is adhesions to the endometrium from the results of uterine repair, HSG, SIS or hysteroscopy can also be done in assessing the success of metroplasty in this patient.Conclusion : After metrosplasty in a patient with a bicornu uterus, further follow-up is required to determine the success of this procedure by performing a follow-up ultrasound.Keywords: Bicornu uterus, metroplasty